ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KONSUMEN DALAM MENGKONSUMSI BERAS ORGANIK DI KOTA BATURAJA OKU (Program Studi Agribisnis Fakultas Pertanian Universitas Baturaja, 2018)
Analysis of Factors Affecting Consumers in Consuming Organic Rice in Baturaja OKU City. This study aims to analyze the Factors Affecting Consumers in Consuming Organic Rice in Baturaja OKU City. The research method used in this research is the field survey method in minimarket Baturaja city. The sampling method used is the accidental sampling method anyone who by chance meet can be used as a sample. The results showed that the factors that significantly affect the consumption of organic rice at consumers in the City of Baturaja is the price factor on the regression test has a negative regression coefficient of negative -0.826 and significant value of 0,000 significant effect on the level of 0.05, income factor at Regression test results have positive regression coefficient of 0.001 and significant value of 0,000 significant effect on the level of 0.05, health factors on regression test results have regression coefficient has a positive effect of 1.209 and significant value of 0.016 have a significant effect on the level of 0.05